Peptide Vaccine Combined Adjuvants Modulate Anti-tumor Effects of Radiation in Glioblastoma Mouse Model - Tran, Thi-Anh-Thuy; Kim, Young-Hee; Duong, Thi-Hoang-Oanh; Jung, Shin; Kim, In-Young; Moon, Kyung-Sub; Jang, Woo-Youl; Lee, Hyun-Ju; Lee, Je-Jung; Jung, Tae-Young (Frontiers in Immunology, 2020)
Glioblastoma, the most common aggressive cancer, has a poor prognosis. Among the current standard treatment strategies, radiation therapy is the most commonly recommended. However, it is often unsuccessful at completely eliminating the cancer from the brain. A combination of radiation with other treatment methods should therefore be considered. It has been reported that radiotherapy in combination with immunotherapy might show a synergistic effect; however, this still needs to be investigated. In the current study, a “branched multipeptide and peptide adjuvants (such as pan DR epitope (PADRE) and polyinosinic-polycytidylic acid—stabilized with polylysine and carboxymethylcellulose—(poly-ICLC))”, namely vaccine and anti-PD1, were used as components of immunotherapy to assist in the anti-tumor effects of radiotherapy against glioblastomas. With regard to experimental design, immunological characterization of GL261 cells was performed and the effects of radiation on this cell line were also evaluated. An intracranial GL261 mouse glioma model was established, and therapeutic effects were observed based on tumor size and survival time. The distribution of effector immune cells in the spleen, based on cytotoxic T lymphocyte (CTL) and natural killer (NK) cell function, was determined. The pro-inflammatory and anti-inflammatory cytokine production from re-stimulated splenocytes and single tumor cells were also evaluated. As GL261 cells demonstrated both immunological characteristics and radiation sensitivity, they were found to be promising candidates for testing this combination treatment. Combinatorial treatment with radiation, vaccine, and anti-PD1 prolonged mouse survival by delaying tumor growth. Although this combination treatment led to an increase in the functional activity of both CTLs and NK cells, as evidenced by the increased percentage of these cells in the spleen, there was a greater shift toward CTL rather than NK cell activity. Moreover, the released cytokines from re-stimulated splenocytes and single tumor cells also showed a shift toward the pro-inflammatory response. This study suggests that immunotherapy comprising a branched multipeptide plus PADRE, poly-ICLC, and anti-PD1 could potentially enhance the anti-tumor effects of radiotherapy in a glioblastoma mouse model.